ANALISIS PENGARUH BEBAN PAJAK KINI DAN PAJAK TANGGUHAN TERHADAP LABA BERSIH PADA PERUSAHAAN AGRIBISNIS YANG TERDAFTAR DI BEI PERIODE TAHUN 2012-2014 - Achmad Hidayat (JURNAL LENTERA AKUNTANSI, 2018)
ABSTRACTThis study aims to determine the effect of current tax expense and deferred tax partially or simultaneously to net income in the agribusiness companies. Poupulasi used in this research is the the agribusiness companies listed on Indonesia Stock Exchanges 2012- 2014 with a sample of 13 companies that have selected using purposive sampling method. This data is in the form of quantitative data is secondary data obtained from the financial statements of the Indonesia Stock Exchange. This study used multiple linear regression analysis with partial testing and simultaneously. These results indicate that the current tax expense and deferred tax and the partiallyand simultaneously effect on net income, so the two independent variables can be used to assess the value of net income that would be obtained agribusiness companies.Keywords: Current tax, Deffered tax, Net income